Corn oil enhances progesterone and estradiol plasma levels in tropical hair sheep - meza villalvazo, Victor manuel; Rojas Marquez, Crystelli Alicia; Sandoval Castro, Carlos; Magana Sevilla, Hector; Trejo Cordova, Alfredo (Ecosistemas y Recursos Agropecuarios, 2018)
The objective of the present study was to evaluate the inclusion of corn oil in the diet of sheep and its eect on serum levels of progesterone and estradiol, Twenty-one Pelibuey sheeps were divided into three treatments based on the level of oil included in the diet (T0 = 0, T3 = 3 and T6 = 6% respectively, on dry basis). Blood samples were obtained to determine hormones in serum. Cholesterol and progesterone were higher for T3 and T6 treatments (p < 0.05) compared to T0. Insulin was higher (p < 0.05) in the T6 treatment compared to treatments T3 and T0. At the time of ovulation, estradiol concentration was higher (p < 0.05) for treatments T3 and T6 compared to T0. The inclusion of corn oil in the diet increases the levels of cholesterol, progesterone, estradiol and insulin in sheep hair.